Propuesta de ahorro energético en el sistema de vapor para la planta de Coopeagropal R.L - Umaña-Salas, Cristofer (Instituto Tecnológico de Costa Rica, 2017)
The project was conducted in Coopeagropal R.L., which is a company dedicated to the extraction and refining of palm oil, located in El Roble de Laurel, Corredores. There, a study of the steam network is carried out to determine the feasibility of implementing a condensate return system, as a way to save energy, water and fuel; which includes an analysis of the possible areas of implementation, as well as the equipment whose operation allows the recovery of clean condensate. The design of a return system is carried out, taking into account the areas where a greater recoverable condensate is generated, as in the refineries and storage tanks for the final product. The design includes the selection and size of steam traps in equipment, selection of pipes, flash steam tanks and mechanical condensate pumps, with a total project cost of ₡ 8 817 416. It was determined that 3,624 tons of condensate could be returned to the boiler and, in turn, the economic savings that this brings with it, including the decrease in water consumption by at least 14% and biomass by 2.3%, to obtain a return on investment in just 10 months after installation. In addition, the economic factor is not the only positive thing in the possible implementation of a system like this, so that a decrease in the consumption of biomass implies a lower amount of processed ash, as well as the amount of water that is subtracted from the planet, which is of great help for the conservation of the environment.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Vapor; Trampas; Biomasa; Diseño; Agua; Research Subject Categories::TECHNOLOGY::Engineering mechanics